Formação e atuação do psicólogo nos hospitais e maternidades do estado de Sergipe - Santos, Lyvia de Jesus (2011)
Health Psychology and Hospital Psychology have trajectories of practice and expertise, sometimes interconnected, sometimes disconnected at all. Therefore, it was considered necessary to get acquainted with the possibilities of intervention within psychologist s professional practice and both theoretical and practical training elements which reinforce professional practice in hospitals with the purpose of analyzing the training process and professional practice of psychologists working in hospitals and maternity wards in the State of Sergipe, within the hospital psychology field. The population definition of this study is made of 29 psychologists working in hospitals and maternity wards of the state of Sergipe. A quanti-qualitative research was elected. A mixed survey figured as the research instrument. Regarding the answers of the closed questions, a descriptive analysis, from the data presented in absolute and in relative frequency, was conducted. However, the answers of open questions were analysis on the thematic approach. The research data were arranged in themes: Training in Hospital Psychology (perception over the training process qualification; training and qualification to work at hospitals) Professional practice in Hospital Psychology (professional practice, difficulties and capability to work at hospitals) and its analytical categories. The sample of the study is characterized as young, varying from 24 to 34 years old (52%) and female in its majority (83%). It was observed that 72,4% of these professionals work for the public health system, 20,6% of them work for private health institutions, 6,8% work for both private and public health institutions. According to the respondents, only 11% of them had the subject Hospital Psychology in their college syllabus and 21 % of them mention the need for boosting their career esteem, as well as they point out the search for undergraduate courses capable of meeting the needs of the labor market. Regarding their qualification, 90 % of the respondents classified it as Good and 10 % as Average (10%). The research background had its foundation in academic formation associated to graduate school courses, professional experience and practical qualification during graduate course. The results of the research pointed out that the psychology s graduate syllabus does not provide the required tools to meet the needs of the psychologist career in health institutions; The challenges in conducting interventions are possible through the confrontation between theory and career practice within the health system and culminates in the ability to search for alternatives and strategies to overcome impasses and difficulties. The transformation lies in, according to the same, in formation with subjects that are focused in health, interchanges between universities and hospitals, internships, supervisions with trained professors, participating in conferences and academic research and being subjected to psychotherapy.